Secondary Syphilis in Human Immunodeficiency Virus (HIV)-Infected Men Who Have Sex with Men (MSM): A Case Report - Ade Fernandes; Evy Ervianti (Berkala Ilmu Kesehatan Kulit dan Kelamin, 2020)
Background: Recently, the incidence of syphilis among men who have sex with men (MSM) has increased rapidly, especially among Human Immunodeficiency Virus (HIV)-infected MSM. Coinfection with these two organisms alter the symptoms and signs, progression of the disease, and the risk of progressing to the tertiary stage. Purpose: To report a case of secondary syphilis in HIV-infected MSM.  Case: A 24-year-old male complaint of multiple redness macule for 1-month duration on his chest, back, groin, palm, and soles. The rash was neither painful nor pruritic. He also complains of hair loss resulting "moth eaten" alopecia. One month before, he had a painless ulcer on his genital, which resolved without treatment. His HIV infection was diagnosed two years earlier. He had been sexually active with multiple homosexual partners without using a condom since 2010. The Venereal Disease Research Laboratory test (VDRL) titer was 1/32, and Treponema pallidum haemagglutination assay (TPHA) was 1/20480. Initial treatment was a single dose of 2.4 million units of benzathine penicillin. Serologic examination was reevaluated on month 1, 3, 6, and 9 after therapy and declined in the third month. Discussion: For HIV-infected persons, the clinical manifestations of syphilis in most of the cases remain the same. However, the lesions are more aggressive, and coexistence of primary and secondary syphilis is more frequent. Serologic tests are accurate and reliable for the diagnosis and for following a patient’s response to treatment. Penicillin is effective but physical and serological follow up is needed. Conclusion: HIV-infected MSM have higher risk of syphilis. Staging is needed to determine the treatment. Serologic examination should be repeated and long enough to monitor the treatment success.